Mindful Leader Development: How Leaders Experience the Effects of Mindfulness Training on Leader Capabilities - Rupprecht, Silke; Falke, Pia; Kohls, Niko; Tamdjidi, Chris; Wittmann, Marc; Kersemaekers, Wendy (Frontiers in Psychology, 2019)
Mindfulness training is a novel method of leader development but contrary to its rising popularity, there is a scarcity of research investigating how mindfulness training may affect leader capabilities. To gain a better understanding of the potential of a new research field, qualitative research is advantageous. We sought to understand how senior leaders experience the impact of mindfulness training in their work lives and leadership ability. The sample comprised 13 leaders (n=11 male) working in six organizations that completed a 10-week workplace mindfulness training (WMT). We conducted semi-structured interviews six to twelve months following course completion. We analysed the data following thematic analysis steps and based on these findings, we devised a framework of the perceived impact of mindfulness training on self-leadership and leadership capabilities. We show that WMT exhibited impact on three self-leadership capacities: mindful task management, self-care and self-reflection and two leadership capacities: relating to others and adapting to change. Participants’ recounts additionally suggested effects may expand to the level of the team and the organisation. We show that WMT may be a promising tool for self-directed leadership development and outline avenues for future research.